The Correlation Between Fetal Wellbeing and Umbilical Doppler Parameters in Pregnant Women with Gestational Hypertension - Lin H; Shen M; Li D; Sun Q; Lan L (International Journal of Women's Health)
Hualan Lin, Meifang Shen, Dongbei Li, Qiuxia Sun, Liubing Lan Obstetrical Department, Meizhou people’s Hospital, Meizhou City, Guangdong Province, 514000, People’s Republic of ChinaCorrespondence: Liubing Lan, Obstetrical Department, Meizhou people’s Hospital, No. 23, Huangtang Road, Meijiang District, Meizhou City, Guangdong Province, 514000, People’s Republic of China, Email lanliubing@126.comObjective: To investigate the role of umbilical cord blood flow parameters in evaluating intrauterine fetal hypoxia and fetal growth restriction in pregnant women with gestational hypertension.Methods: One hundred and nine patients with gestational hypertension admitted from January 2020 to December 2023 were enrolled in this study. The peak systolic velocity/end diastolic velocity (S/D), pulse index (PI) and resistance index (RI) of cord blood were measured by ultrasound. According to the S/D, 109 cases were divided into 62 cases in the control group (S/D < 3) and 47 cases in the observation group (S/D ≥ 3), and the prognosis of pregnant women and fetuses in the two groups were compared. The ROC curves were used to analyze the effects of different parameters of umbilical blood flow on intrauterine fetal hypoxia and fetal growth restriction in pregnant women with gestational hypertension.Results: The incidence of intrauterine fetal hypoxia, fetal growth restriction, cesarean section, and unresponsive type of non-irritation test was decreased in the control group compared with the observation group (P < 0.05). However, there was no statistical difference in the incidence of neonatal asphyxia between the two groups (P > 0.05). ROC curve analysis showed that cord blood flow RI of pregnant women with gestational hypertension had the highest sensitivity and AUC in predicting intrauterine fetal hypoxia and growth restriction, and PI had the highest specificity in predicting intrauterine fetal growth restriction. The specificity of S/D, PI and RI in predicting intrauterine hypoxia was consistent (all 80%).Conclusion: The different parameters of umbilical blood flow in hypertensive pregnant women during pregnancy provide a good assessment of intrauterine fetal condition and can be used as clinical indicators to predict poor prognosis of intrauterine fetal hypoxia and fetal growth restriction.Keywords: gestational hypertension, hypoxia, growth restriction, umbilical blood flow, assessment